Power and influence in India bosses, lords and captains - Price, Pamela G.; Ruud, Arild Engelsen (Exploring the political in South Asia, 2010)
The importance of individual leaders in the projection of politics in South Asia is evident from how political parties, mobilisation of movements and the media all focus on carefully constructed personalities. Besides, the politically ambitious have considerable room for manoeuvre in the institutional setup of the Indian subcontinent. This book focuses on actors making their political career and/or aspiring for leadership roles, even as it also foregrounds the range of choices open to them in particular contexts. The articles in this volume explore the variety of strategies used by politically engaged actors in trying to acquire (or keep) power - symbolic action, rhetorical usage, moral conviction, building of alliances - illustrating, in the process, both the opportunities and constraints experienced by them.